Risk Factors of Cervical Cancer in Outpatient and Inpatient at Obstetric and Gynecology RSUP Dr. Mohammad Hoesin Palembang - Trifitriana, Monica; Sanif, Rizal; Husin, Syarif; Mulawarman, Rido (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction: Cervical cancer is a malignant tumor originating from primary squamous epithelial cells and it is one of the several types of cancers that affects more to women. Methods: This research uses descriptive analytic with case- control. The sample was 52 patients who divided into 26 patients with cervical cancer and 26 patients with non - cervical cancer were outpatient and inpatient at Department of Obstetrics and Gynecology Hospital Dr. Mohammad Hoesin Palembang during the period September 2016 -November 2016. This study uses primary data in the form of interviews. Data was analyzed by univariate and presented in a frequency distribution table. Furthermore, using bivariate analysis to determine the relationship and OR. Result: From 8 risk factors studied, there is sygnificancy correlation between pathological vaginal discharge (p= 0,0005 OR= ∞), parity (p= 0,0005 OR= 22,7), age (p= 0,0005 OR= 19,2), oral contraception usage for a long time (p= 0,0005, OR= 12,4), age of the first intercourse (p= 0,006, OR= 6,1 ), and the husband’s occupation (p= 0,05 OR= 3,6) with the incidence of cervical cancer. While, there are two risk factors that don’t have a sygnificancy correlation between smoking (p= 1,0) and changing sexual partners (p= 1,0) with the incidence of cervical cancer. Conclusion: The results of this research identified risk factors that significantly related to cervical cancer incidence was the age, the age of first sexual intercourse, parity, long-term oral contraceptive use, a history of vaginal discharge, and the husband's occupation.